2020
DOI: 10.48550/arxiv.2009.04058
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning topological invariants of non-Hermitian systems

Ling-Feng Zhang,
Ling-Zhi Tang,
Zhi-Hao Huang
et al.

Abstract: The study of topological properties by machine learning approaches has attracted considerable interest recently. Here we propose machine learning the topological invariants that are unique in non-Hermitian systems. Specifically, we train neural networks to predict the winding of eigenvalues of three different non-Hermitian Hamiltonians on the complex energy plane with nearly 100% accuracy. Our demonstrations on the Hatano-Nelson model, the non-Hermitian Su-Schrieffer-Heeger model and generalized Aubry-André-Ha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…Note added-After finalizing this work, we became aware of a complementary study by Zhang et al [62]. Where overlapping, our results are consistent with theirs.…”
supporting
confidence: 81%
“…Note added-After finalizing this work, we became aware of a complementary study by Zhang et al [62]. Where overlapping, our results are consistent with theirs.…”
supporting
confidence: 81%
“…Recently, machine learning fuelled by algorithmic advances and increasing computer power [480] has been proven useful for designing and predicting various topological phases of matter [481][482][483][484]. It is shown that physical properties of the Hatano-Nelson models, the Aubry-André-Harper models [485], the 1D non-Hermitian SSH models and the 3D non-Hermitian semimetals [486] (nodal lines) can be predicted by identifying the non-Hermitian topological indicators in terms of fully connected neural networks (with the accuracy 99.9%) or convolutional neural networks (with the accuracy 99.8%). Unsupervised learning has also been proposed to classify non-Hermitian skin effects by distinguishing the vanishing diffusion probabilities, which guides both theories and experiments [487].…”
Section: Othersmentioning
confidence: 99%
“…The Ref. [22,[25][26][27][28][29] focus on the Su-Schrieffer-Heeger (SSH) model [31,32] which is also the subject of this work.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [21,22,[25][26][27][28][29][30] are examples of recent work on identifying topological phases and phase transitions using either neural networks or diffusion maps. The Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation